1996
DOI: 10.1007/bf00327716
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining rock phosphate solubilization by microorganisms isolated from soil

Abstract: Forty two soil isolates (31 bacteria and 11 fungi) were studied for their ability to solubilize rock phosphate and calcium phosphate in culture medium. Eight bacteria and 8 fungi possessed solubilizing ability. Pseudomonas cepacia and Penicillium purpurogenum showed the highest activity. There was a correlation between final pH value and titratable acidity (r=-0.29 to -0.87) and between titratable acidity and soluble phosphate (r=0.22 to 0.99). Correlation values were functions of insoluble phosphate and of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
105
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(122 citation statements)
references
References 19 publications
8
105
0
9
Order By: Relevance
“…Fungi are the important components of soil microbes typically constituting more of the soil biomass than bacteria, depending on soil depth and nutrient conditions. Fungi have been reported to have greater ability to solubilize insoluble phosphate than bacteria [6]. A wide range of soil fungi are reported to solubilize insoluble phosphorous such as Aspergillus niger and Penicillium sp., which are the most common fungi capable of phosphate solubilization [7].…”
Section: Introductionmentioning
confidence: 99%
“…Fungi are the important components of soil microbes typically constituting more of the soil biomass than bacteria, depending on soil depth and nutrient conditions. Fungi have been reported to have greater ability to solubilize insoluble phosphate than bacteria [6]. A wide range of soil fungi are reported to solubilize insoluble phosphorous such as Aspergillus niger and Penicillium sp., which are the most common fungi capable of phosphate solubilization [7].…”
Section: Introductionmentioning
confidence: 99%
“…The lower positive response of the clayey soil (RC value) to the applied bioorganic additives, than the sandy soil, could be due to its sorption-desorption capacity, controlling the equilibrium dynamics of phosphates in soil solution (Lindsay, 1979). Nahas (1996), Khan et al (2007) and Muhammad & Maram (2012) concluded that phosphate solubilizing bacteria "PSB" and organic fertilizers were effective on solubilizing rock phosphate, by decreasing the pH of the soil treated with rock phosphate, through production of carbonic and organic acids. Moreover, the polycarboxylic organic metabolites might hinder the activity of Ca cations via chelating reaction, in favour to P solubilization.…”
Section: Effect Of the Bio-organic Additives On Soluble Phosphate Conmentioning
confidence: 99%
“…Their application in several crop tend to increase their yield in crop such as cereals, legume, vegetable, fruit crops (Kundu et al, 2009). Phosphate solubilising microorganisms release metabolite such as organic acid latter being converted into the soluble form (Nahas, 1996). Phosphate solubilising microorganisms dissolve soil P through production of low molecular weight organic compound mainly gluconic and ketogluconic acid (Khan et al, 2009).…”
Section: Phosphorus Producing Biofertilizermentioning
confidence: 99%